Risk Factors of Attention Deficit Hyperactivity Disorder (ADHD) among Children in Denpasar - I Made Sudarma Adiputra; I Made Sutarga; Gede Ngurah Indraguna Pinatih (Universitas Udayana, 2015)
Background and purpose: Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder that often occurs in children characterized by low concentration and hyperactivity. Comprehensive efforts required to prevent and to understand risk factor of ADHD. Aim of this study was to understand risk factors that may increase the occurrence of ADHD among children in Denpasar. Methods: The study design was a matched case-control. Number of samples was 38 cases and 38 controls, who were matched by age, sex and residence. Cases was obtained from the Service Center of Psychology and Children with Special Needs Pradnyagama Denpasar. Controls were selected from the residence close to cases. Data analysis was performed with the McNemar test and conditional (fixed-effects) logistic regression. Results: The study found that there were two factors significantly increase risk of ADHD namely low birth weight (adjusted OR=220.9; 95%CI: 6.9-6991,3) and genetic (adjusted OR=45.5; 95% CI: 3.3-620.9). Conclusions: Low birth weight and genetic were found as risk factorsof ADHD.